Relationship between T1 slope and loss of lordosis after laminoplasty in patients with cervical ossification of the posterior longitudinal ligament - Kim, Byeongwoo; Yoon, Do Heum; Ha, Yoon; Yi, Seong; Shin, Dong Ah; Lee, Chang Kyu; Lee, Nam; Kim, Keung Nyun (The spine journal, 2016)
Laminoplasty is a major surgical method used to treat patients with cervical ossification of the posterior longitudinal ligament (OPLL). Sometimes, patients with cervical OPLL demonstrate postoperative kyphosis despite sufficient preoperative lordosis. Recently, the impact of T1 slope has emerged as a predictor of kyphotic alignment change after laminoplasty. However, the relationship between T1 slope and postoperative cervical alignment change is not yet fully established. The goals of the present study were to investigate the relationship between T1 slope and loss of cervical lordosis (LCL), and to identify the role of T1 slope as a predictor of postoperative kyphosis after laminoplasty in patients with OPLL. This is a retrospective case study. Between January 2011 and January 2012, 64 consecutive patients who underwent cervical laminoplasty for OPLL were enrolled (male:female ratio=47:17; mean age=55.9 years). Cervical spine lateral radiographs in neutral, flexion, and extension were taken before surgery and at 2-year follow-up. The C2–C7 Cobb angle, cervical range of motion (ROM), T1 slope, neck tilt, and C2–C7 sagittal vertical axis (SVA) were measured from lateral radiographs of the cervical spine preoperatively and postoperatively at 2-year follow-up. Patients were divided into two groups according to preoperative T1 slope, and the postoperative cervical alignment change was compared between the groups. Postoperative kyphosis and LCL incidence were also evaluated at 2-year follow-up. The relationships between postoperative cervical alignment change and preoperative variables, including age, T1 slope, cervical ROM, C2–C7 SVA, and T1 slope minus C2–C7 Cobb angle (T1S−CL), were investigated. Patients were divided into two groups above and below median preoperative T1 slope (23.2°). There were no differences in age, sex, type of OPLL, or operation level between the two groups. Patients with higher preoperative T1 slope demonstrated significantly more lordotic preoperative cervical alignment (p=.001). Patients with higher preoperative T1 slope were more likely to exhibit postoperative LCL (p=.03), and when it occurred the degree of LCL was greater (p=.06). In multiple linear regression analysis, higher T1 slope (B=0.414, p=.04) and lower T1S−CL (B=−0.412, p=.03) were significantly associated with more postoperative LCL. In spite of these results, postoperative kyphosis did not occur more frequently in patients with higher T1 slope (p=.64). Patients with higher T1 slope had more lordotic curvature before surgery and demonstrated more LCL at 2-year follow-up. Cervical alignment was compromised after laminoplasty, and the degree of LCL was correlated with preoperative T1 slope. After laminoplasty for cervical OPLL, patients with higher T1 slope tended to exhibit a greater LCL yet did not drift into frank postoperative kyphosis.